2015
DOI: 10.3109/07420528.2015.1008135
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm of intraocular pressure in the adult rat

Abstract: Ocular hypertension is a risk factor for developing glaucoma, which consists of a group of optic neuropathies characterized by progressive degeneration of retinal ganglion cells and subsequent irreversible vision loss. Our understanding of how intraocular pressure damages the optic nerve is based on clinical measures of intraocular pressure that only gives a partial view of the dynamic pressure load inside the eye. Intraocular pressure varies over the course of the day and the oscillator regulating these daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 56 publications
(63 reference statements)
2
18
0
1
Order By: Relevance
“…In the light phase, the IOP in normal eyes measures approximately 20 mmHg by tonopen and TonoLab, while that during the dark is significantly increased to over 30 mmHg. (Kwong et al, 2013; Lozano et al, 2015; Moore et al, 1996; Valderrama et al, 2008) These considerations may apply to mice as well, as Liu has demonstrated higher IOP in the dark in mice monitored telemetrically. (Li and Liu, 2008) However, detailed assessment of this by non-invasive tonometry in awake mice has not yet been performed.…”
Section: Outcomes Of Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the light phase, the IOP in normal eyes measures approximately 20 mmHg by tonopen and TonoLab, while that during the dark is significantly increased to over 30 mmHg. (Kwong et al, 2013; Lozano et al, 2015; Moore et al, 1996; Valderrama et al, 2008) These considerations may apply to mice as well, as Liu has demonstrated higher IOP in the dark in mice monitored telemetrically. (Li and Liu, 2008) However, detailed assessment of this by non-invasive tonometry in awake mice has not yet been performed.…”
Section: Outcomes Of Injectionmentioning
confidence: 99%
“…Fortunately, we have determined that, when animals are housed in a constant, low-light level environment (approximately 90 lux), the innate IOP fluctuation is suppressed. (Lozano et al, 2015; Morrison et al, 2005; Pang et al, 2005b) This maneuver, in addition to reducing one cause of IOP fluctuation, allows the researcher greater latitude on when to measure IOP.…”
Section: Outcomes Of Injectionmentioning
confidence: 99%
“…Eight-month-old Brown Norway rats were housed in constant low-level light according to the standard protocol in our laboratory. This approach was adopted to attenuate circadian fluctuations of IOP 8,51 and to enable meaningful comparison with our previously published data using the same experimental glaucoma model housed in identical light conditions. 8,16,20,52 Aqueous outflow obstruction was created by injecting hypertonic saline unilaterally into episcleral veins, resulting in sustained elevation of IOP.…”
Section: Glaucoma Modelmentioning
confidence: 99%
“… 19 21 They also include processes linked to retina survival such as rhythms in shedding of rod and cone outer segments and phagocytosis by the underlying RPE 22 , 23 and the vulnerability to phototoxicity. 24 In addition, rhythmic processes have been reported elsewhere in the eye, such as in the cornea (daily variation of thickness or mitotic rate 25 , 26 ) and in the ciliary body (aqueous production contributing to intraocular pressure 27 , 28 ). In line with these results, transcriptomics analysis of the eyes over the 24-hour period provided an extensive view of processes under cyclic control in ocular tissues.…”
mentioning
confidence: 99%